2012
DOI: 10.1182/blood-2012-04-423525
|View full text |Cite
|
Sign up to set email alerts
|

Specific lipid mediator signatures of human phagocytes: microparticles stimulate macrophage efferocytosis and pro-resolving mediators

Abstract: IntroductionInflammation is the organisms' response to local injury in vascularized tissues programmed to traffic leukocytes and plasma delivery to an injured site or point of bacterial invasion, 1 this protective response when uncontrolled in humans is associated with many widely occurring diseases. These include cardiovascular, metabolic, and the classic inflammatory diseases (ie, arthritis and periodontal disease) along with cancers. 2 Nonresolving inflammation is now widely acknowledged as a major driver i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
535
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 455 publications
(562 citation statements)
references
References 49 publications
13
535
1
1
Order By: Relevance
“…RvD3 and its biosynthetic pathway intermediates 4-HDHA and 17-HDHA were identified in accordance with published criteria, 14 including retention time and MS-MS fragmentation spectra (Figure 1, A and B). Relative to uninjured lungs, 4-HDHA and 17-HDHA increased approximately twofold to threefold 24 hours after injury, returning to baseline levels at 72 hours ( Figure 1C Figure 1D).…”
Section: Endogenous Rvd3 Is Generated In Response To Acid-induced Lunsupporting
confidence: 75%
“…RvD3 and its biosynthetic pathway intermediates 4-HDHA and 17-HDHA were identified in accordance with published criteria, 14 including retention time and MS-MS fragmentation spectra (Figure 1, A and B). Relative to uninjured lungs, 4-HDHA and 17-HDHA increased approximately twofold to threefold 24 hours after injury, returning to baseline levels at 72 hours ( Figure 1C Figure 1D).…”
Section: Endogenous Rvd3 Is Generated In Response To Acid-induced Lunsupporting
confidence: 75%
“…18,19 We found that M1 and M2 macrophage phenotypes extend to SPMs and eicosanoid profiles. 16 M2 macrophages have elevated levels of pro-resolving lipid mediators and decreased PGs and LTs in relation to M1 macrophages. 16 By analyzing PCTR1 levels in comparison with RCTR, MCTR, and cys-LTs, we identified the distinct peptide-conjugate lipid mediator profiles of human M1 and M2 macrophages, in which pro-resolving peptide-conjugates have a reciprocal relation to the inflammatory cys-LTs ( Figure 8C).…”
Section: Discussionmentioning
confidence: 95%
“…For M1 and M2 macrophage differentiation, the previously published protocol and criteria were used. 16 In brief, M1 macrophages were produced by incubating isolated monocytes with granulocyte-macrophage CSF (20 ng/mL) for 7 days, followed by lipopolysaccharide (1 ng/mL) plus interferon-g (20 ng/mL) treatment for 24 hours. M2 macrophages were obtained by incubating monocytes with 20 ng/mL macrophage CSF for 7 days and then stimulating with 20 ng/mL IL-4 for 48 hours.…”
Section: Cell Isolations and Culturementioning
confidence: 99%
“…In a recent study, PMNderived microparticles were shown to stimulate efferocytosis and production of pro-resolving lipid mediators in macrophages [25].…”
Section: Role Of Pmn-derived Vesicles In Communicationmentioning
confidence: 98%
“…Other chemokines secreted by PMN are chemoattractants to monocytes [102] or lymphocytes [66] triggering the second wave of cell migration, mostly of mononuclear cells. Furthermore, activated neutrophils produce lipid mediators such as resolvins and protectins that inhibit neutrophil recruitment [25,58,66] and "find me" and "eat me" signals that initiate the elimination of aged PMN by macrophages [14].…”
Section: Interaction With Other Immune Cellsmentioning
confidence: 99%